VALIDITY, RELIABILITY AND PRACTICALITY OF THE FIRST CERTIFICATION IN ENGLISH (FCE) AND THE BUSINESS LANGUAGE TESTING SERVICE (BULATS) - Arifin Ahkam Muhammad (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2018)
This paper begins with the test specifications of the two tests – the First Certification in English (FCE) and the Business Language Testing Service (BULATS). It will then go on to the evaluation of the test usefulness: reliability, (construct) validity, backwash, and practicality (Bachman & Palmer, 1996; see Kunnan, 2004 for a slightly different perspective). This paper explores the test specifications at the outset in that a test would be evaluated (as estimated) based on the test purpose and construct that it is trying to measure (Luoma, 2004). To begin the evaluation, the test (score) reliability would be evaluated first, for a test would not be considered valid if it is not reliable (Brown, 1996; but see Moss, 1994 when a test could be valid without reliability). Throughout this paper, the term “test(ing)” will be used more or less synonymously with “assess(ment)” and “measure(ment)”, in that Bachman and Palmer point out that in the field of language testing these terms have been very broadly defined “as the process of collecting information” to make decisions (2010, p. 20). (See Bachman, 1990; Cohen & Swedlik, 2010; Douglas, 2010 for the distinctions, e.g., a test is a tool for assessment.)